Pengaruh kompetensi profesional dan motivasi kerja terhadap kinerja guru smk di kabupaten tapanuli utara - Khristopel Simamora; Pardomuan Simanullang; Rencan Carisma Marbun (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This study aims to determine 1) the influence of professional competence on the performance of vocational high school teachers in North Tapanuli Regency; 2) the influence of work motivation on the performance of vocational high school teachers in North Tapanuli Regency; and 3) the joint influence of professional competence and work motivation on the performance of vocational high school teachers in North Tapanuli Regency. This study used a quantitative survey method. The population was 81 vocational high school teachers, consisting of 62 teachers from State Vocational High School 1, Siborongborong District, and 19 teachers from State Vocational High School 1, Muara District, North Tapanuli Regency. The sample of this study was a saturated sample of 81 people. Data were collected with a closed questionnaire consisting of 55 statement items for variable Y (Teacher Performance) and 54 statement items for variable X1 (Professional Competence) and 20 statement items to measure variable X2 (Work Motivation), so that the total was 129 statement items. Before being used on real respondents, the instrument was first tested on 30 State Vocational High School 1 Teachers, Pagaran District, North Tapanuli Regency. The results of the instrument trial showed that all questionnaire items were valid and reliable. Data analysis techniques were carried out using descriptive analysis, variable categorization and parametric statistical analysis with simple and multiple linear regression by looking at the value of the linear equation, correlation value and coefficient of determination as well as t-test and F-test. The results of the data analysis show that: 1) Teacher Professional Competence has a positive effect on the Performance of Vocational High School Teachers in North Tapanuli Regency with a contribution of 28.3%, where the strong correlation value is 0.532, with a linear equation of Y = 83.056 + 0.610X1 and t count = 5.557> t table (n-2 = 79) = 2.000. 2) Work Motivation has a positive effect on the Performance of Vocational High School Teachers in North Tapanuli Regency in 2016 with a contribution of 32.6%, where the strong correlation value is 0.571, with a linear equation of Y = 108.072 + 1.278 and t count = 6.182> t table (n-2 = 79) = 2.000 and 3) Professional Competence and Teacher Work Motivation together have a positive effect on the Performance of Vocational High School Teachers in North Tapanuli Regency with a contribution of 42.6% where the strong correlation value of R is 0.653, multiple linear equations Y = 54.546 + 0.403X1 + 0.940X2 and F count = 28.974> F table (k-1, n-k; 2.79) = 3.15. Thus it is concluded that the research hypothesis is accepted.